Heuristics in Self-Evaluation: Evidence from the Centralized College Admission System in China - Li, Hongbin; Qiu, Xinyao (The Review of Economics and Statistics, 2025)
Using administrative data on the Chinese National College Entrance Examination, we study how left-digit bias affects college applications. We find strong discontinuities in students’ admission outcomes at ten-point thresholds. Students with scores just below multiples of 10 make more conservative college application choices that place them into less selective colleges and majors. In contrast, students who score at or just above multiples of 10 aim at and achieve higher but are at greater risk of overshooting. The discontinuity reveals that despite the educational and labor market consequences, students’ self-evaluation based on exam scores is subject to information-processing heuristics.